More public education needed on changes to EP system - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2017)
The office of Singapore’s Elected President is often misunderstood. Although it has been part of our system of institutional checks and balances since 1991, a popular misconception is that the President is a centre of political power unto itself.